A review and analysis of the early nomenclature and taxonomy associated with the genus name Kalanchoe (Crassulaceae subfam. Kalanchooideae), published by Michel Adanson (1727–1806) in 1763, with notes on the late-18 century taxonomy of the genus - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2024)
In 1763 Michel Adanson (1727–1806) published several hundred new genus names, including some in the “Famille Les Jourbarbes. Seda.”, i.e., the present-day Crassulaceae. One of these, Kalanchoe, was published for the then cotyledonoid species with tetramerous flowers. The early nomenclature associated with the validly published and legitimate genus name Kalanchoe and the late-18th century taxonomy of the genus are reviewed. Based on available evidence it is very likely that Adanson was familiar with, and had material at his disposal of, more than one species of Kalanchoe. However, Adanson did not himself validly publish any species names in the genus.